2019
DOI: 10.3390/en12081481
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Willingness to Pay Studies for Climate Change Mitigation in the Energy Sector

Abstract: A wide range of climate change mitigation policies have been developed around the world and these policies have become one of the major concerns, however there is still debate among scientists about what are the main external benefits and how to account for them and prepare effective climate change mitigation policies that might be widely accepted by society in general. One of the main ways to assess external benefit of climate change mitigation in energy sector is to conduct Willingness to Pay (WTP) assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 136 publications
(238 reference statements)
1
16
0
1
Order By: Relevance
“…Regarding the determining variables of the WTP for certified dry firewood, it was found that income is a relevant variable, which is consistent with the literature on the valuation of other sources of alternative energy for households (Johnson and Takama, 2012;Kooser, 2014;Streimikiene et al, 2019;Nduka, 2021). However, we did not find statistically significant evidence that education has an influence, contrary to what was found by authors such as Nduka (2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the determining variables of the WTP for certified dry firewood, it was found that income is a relevant variable, which is consistent with the literature on the valuation of other sources of alternative energy for households (Johnson and Takama, 2012;Kooser, 2014;Streimikiene et al, 2019;Nduka, 2021). However, we did not find statistically significant evidence that education has an influence, contrary to what was found by authors such as Nduka (2021).…”
Section: Discussionsupporting
confidence: 87%
“…According to different authors, the methods of economic valuation have been classified into three categories: direct valuation, indirect valuation, and contingent valuation. The third is what is addressed here (Dixon and Hufschmidt, 1986;James, 1994;Haab and McConnell, 2002;Segerson, 2017;Streimikiene et al, 2019;Cuccia, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 80%
“…For example, a recent study on an Italian nationwide survey shows that WTP ranges a lot and the heterogeneity due to proposed public policies and individual characteristics is similar [35]. While these approaches generally focus on green technologies [28,29], many studies focus on adaptation strategies, such as coastal adaptation policies facing sea-level rise [76,77]. Very recently studies focused on stated preferences started analysing WTP for the adoption of nature-based solutions [30].…”
Section: The Willingness To Pay For Insurance Against Disasters Resulting From Climate Changementioning
confidence: 99%
“…Researchers must develop new approaches to deal with new elements in the valuation process. We expect that climate change, as one of the defining challenges of the 21st century, will attract most attention from researchers to propose new approaches in environmental valuation [41,42]. As knowledge and perception are subjective, the intangible aspects must be explicitly considered in the new valuation methods [13].…”
Section: Discussionmentioning
confidence: 99%